Physical Properties of Nanorods - Krahne, Roman; Manna, Liberato; Morello, Giovanni; Figuerola, Albert; George, Chandramohan; Deka, Sasanka; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Inorganic nanoparticles are among the most investigated objects nowadays, both in fundamental science and in various technical applications. In this book the physical properties of nanowires formed by nanoparticles with elongated shape, i.e. rod-like or wire-like, are described. The transition in the physical properties is analyzed for nanorods and nanowires consisting of spherical and rod-like nanoparticles. The physical properties of nanowires and elongated inorganic nanoparticles are reviewed too. The optical, electrical, magnetic, mechanical and catalytic properties of nanowires consisting of semiconductors, noble and various other metals, metal oxides properties and metal alloys are presented. The applications of nanorods and nanowires are discussed in the book.
Materials and Morphologies of Nanorods and Nanowires -- Quantum Confinement Effects -- Optical Properties -- Electrical and Photoconductive Properties -- Magnetic Properties -- Catalytic Properties -- Mechanical Properties -- Applications of Nanorods and Nanowires -- Conclusions and Outlook.
Keywords: Physics; Chemistry, Physical organic; Engineering; Optical materials; Nanotechnology; Materials; Physics; Nanoscale Science and Technology; Optical and Electronic Materials; Nanotechnology and Microengineering; Nanotechnology; Physical Chemistry; Metallic Materials